Cortical Reorganization Is Associated with Surgical Decompression of Cervical Spondylotic Myelopathy - Andrew Green; Priscilia W. T. Cheong; Stephanie Fook-Chong; Rajendra Tiruchelvarayan; Chang Ming Guo; Wai Mun Yue; John Chen; Yew Long Lo (Neural Plasticity)
Background. Cervical spondylotic myelopathy (CSM) results in sensorimotor limb deficits, bladder, and bowel dysfunction, but mechanisms underlying motor plasticity changes before and after surgery are unclear. Methods. We studied 24 patients who underwent decompression surgery and 15 healthy controls. Patients with mixed upper and lower limb dysfunction (Group A) and only lower limb dysfunction (Group B) were then analysed separately. Results. The sum amplitude of motor evoked potentials sMEP (p<0.01) and number of focal points where MEPs were elicited (N) (p<0.001) were significantly larger in CSM patients compared with controls. For Group A (16 patients), sMEP (p<0.01) and N (p<0.001) showed similar findings. However, for Group B (8 patients), only N (p=0.03) was significantly larger in patients than controls. Group A had significantly increased grip strength (p=0.02) and reduced sMEP (p=0.001) and N (p=0.003) after surgery. Changes in sMEP (cMEP) significantly correlated inversely with improved feeding (p=0.03) and stacking (p=0.04) times as was the change in number of focal points (NDiff) with improved writing times (p=0.03). Group B did not show significant reduction in sMEP or N after surgery, or significant correlation of cMEP or NDiff with all hand function tests. No significant differences in H reflex parameters obtained from the flexor carpi radialis, or central motor conduction time changes, were noted after surgery. Discussion. Compensatory expansion of motor cortical representation occurs largely at cortical rather than spinal levels, with a tendency to normalization after surgery. These mirrored improvements in relevant tasks requiring utilization of intrinsic hand muscles.